Implementation of the Process Oriented Guided Inquiry Learning With Socioscientific Issues of Environmental Pollution to Improve Student Scientific Literacy - Pradina Anggi, Oktari; ., Hernani; Solihat, Rini (KnE Social Sciences, 2024)
This study aimed to analyze the implementation of the Process Oriented Guided Inquiry Learning (POGIL) model with the Socioscientific Issues (SSI) of environmental pollution in an effort to improve students’ scientific knowledge. The population in this research was 53 grade VII students at a junior high school in Bandung. The research used a quasi-experimental design with 24 multiple choice questions as the research instrument. The experimental group was taught through the POGIL model with the SSI context, while the control group was taught through a scientific approach. Based on data analysis, the n-gain category of scientific knowledge of the experimental class in content knowledge, procedural, and epistemic domains were dominant in the medium category of 50%, high of 46%, and high of 73%. The n-gain category of the control class in content knowledge, procedural, and epistemic domains was dominant in the low category of 52%, low of 41% and high of 67%. The result obtained from the t-test on normal and homogenous data showed that there was a significant difference. Based on the data analysis, the scientific literacy skill of students who received POGIL with SSI was better than students who received the scientific approach, and the attainment of students’ scientific knowledge domains was in the high category. Keywords: implementation, inquiry learning, socioscientific issues, environmental pollution, student Literacy